Warunki mieszkaniowe jako wyznacznik jakości życia osób niepełnosprawnych na przykładzie osób z dysfunkcją narządu wzroku - Sadowa, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
One of the basic needs of a person is to have a place to live. Virtually everyone dreams of having their own place, to relax and feel safe. Such a space is an important place for people with disabilities, because it is often the only place that is tailored to their needs, where they feel safer than in any other spaces. Every citizen of the country has the right to housing, which is provided by numerous documents and regulations. The purpose of this article is to evaluate the impact of housing conditions on the quality of life of people with disabilities. The following thesis has been formulated in the work: the disabled aim to improve the quality of their lives by changing housing conditions. Literature sources have been reviewed to define basic concepts, the results of previous studies have been correlated. After accessing the database, the results of the research carried out in March 2015 by the foundation “Nie widzę problemu” (literally meaning “I do not see the problem”) with involvement of employees and students of the University of Wroclaw have been compiled. The analysis shows that respondents most often live together with their parents and spend a large part of their income on purchases related to household appliances. As much as 60% of respondents do not own a flat. Approximately 68% find the buildings they live in are not suited to their needs, however only 23% of them try to get social housing
Keywords: niepełnosprawność; dysfunkcje wzroku; jakość życia; warunki mieszkaniowe; potrzeby mieszkaniowe